Implementation of Time Performance Control, Donator System, and Coordination Level in Mosque Construction in Indonesia - Pratama, Enif Asfarianto; Suroso, Agus (ASTONJADRO, 2025)
The process of building a mosque requires competent human resources and community participation. In addition, the availability of funds and support from the government or local authorities can also affect the duration of mosque construction. This study aims to analyze the effect of change orders on the availability of human resource skills and project implementation time performance in West Nusa Tenggara. The research method with quantitative surveys to determine the relationship between change orders, availability of HR skills and time performance will be made in a path diagram model, and analyzed using SEM-PLS with a sample of 104 respondents. The results of the study indicate that design, donors, and coordination together have a significant influence on change orders in mosque construction projects. Change orders in mosque construction projects have a significant impact on human resources, Human resource competence has a significant influence on the time performance of mosque construction projects and Controlling design, donor, and coordination variables is the key to reducing the frequency of order changes, increasing human resource competence, and ensuring optimal time performance in mosque construction projects.